Phenotypic and Functional Plasticity of CXCR6+ Peripheral Blood NK Cells - Angelo, Laura S.; Hogg, Graham D.; Abeynaike, Shawn; Bimler, Lynn; Vargas-Hernandez, Alexander; Paust, Silke (Frontiers in Immunology, 2022)
Human NK cells are comprised of phenotypic subsets, whose potentially unique functions remain largely unexplored. C-X-C-motif-chemokine-receptor-6 (CXCR6)+ NK cells have been identified as phenotypically immature tissue-resident NK cells in mice and humans. A small fraction of peripheral blood (PB)-NK cells also expresses CXCR6. However, prior reports about their phenotypic and functional plasticity are conflicting. In this study, we isolated, expanded, and phenotypically and functionally evaluated CXCR6+ and CXCR6– PB-NK cells, and contrasted results to bulk liver and spleen NK cells. We found that CXCR6+ and CXCR6– PB-NK cells preserved their distinct phenotypic profiles throughout 14 days of in vitro expansion (“day 14”), after which phenotypically immature CXCR6+ PB-NK cells became functionally equivalent to CXCR6– PB-NK cells. Despite a consistent reduction in CD16 expression and enhanced expression of the transcription factor Eomesodermin (Eomes), day 14 CXCR6+ PB-NK cells had superior antibody-dependent cellular cytotoxicity (ADCC) compared to CXCR6– PB-NK cells. Further, bulk liver NK cells responded to IL-15, but not IL-2 stimulation, with STAT-5 phosphorylation. In contrast, bulk splenic and PB-NK cells robustly responded to both cytokines. Our findings may allow for the selection of superior NK cell subsets for infusion products increasingly used to treat human diseases.